2017
DOI: 10.1242/dev.149443
|View full text |Cite
|
Sign up to set email alerts
|

FGF receptors control alveolar elastogenesis

Abstract: Alveologenesis, the final step of lung development, is characterized by the formation of millions of alveolar septa that constitute the vast gas-exchange surface area. The genetic network driving alveologenesis is poorly understood compared with earlier steps in lung development. FGF signaling through receptors and is crucial for alveologenesis, but the mechanisms through which they mediate this process remain unclear. Here we show that in () global mutant mice, alveolar simplification is first observed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 59 publications
(84 reference statements)
0
36
0
Order By: Relevance
“…In addition, since the Tbx4rtTA;TetOCre allele exclusively deletes in the lung mesenchyme, our data provide strong support that the mesodermally derived lung fibroblasts are the primary drivers of elastogenesis during early postnatal stages. The precise organization of the alveolar ECM is essential for proper alveolar development (40)(41)(42)(43)(44)(45). Our data show no differences in the formation of any of the alveolar ECM components in conditional Hox5 mutants except for disruption of the elastin matrix.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, since the Tbx4rtTA;TetOCre allele exclusively deletes in the lung mesenchyme, our data provide strong support that the mesodermally derived lung fibroblasts are the primary drivers of elastogenesis during early postnatal stages. The precise organization of the alveolar ECM is essential for proper alveolar development (40)(41)(42)(43)(44)(45). Our data show no differences in the formation of any of the alveolar ECM components in conditional Hox5 mutants except for disruption of the elastin matrix.…”
Section: Discussionmentioning
confidence: 57%
“…The Elastin-Based ECM Network Is Severely Disrupted in Hox5 Triple-Mutant Distal Lungs. Previous studies have shown that the ECM plays a fundamental role in coordinating proper alveologenesis in the distal lung (40)(41)(42)(43)(44)(45). We, therefore, analyzed several key ECM components in conditional P0-P7 Dox-treated Hox5 triplemutant mice and compared them with controls.…”
Section: Hox5 Genes Exhibit Highest Levels Of Expression During Earlymentioning
confidence: 99%
“…Elastogenesis is a complex and highly regulated process (Sproul and Argraves, 2013). Disrupted elastogenesis leads to abnormal alveologenesis (Wendel et al, 2000;McGowan and McCoy, 2014;Li et al, 2017). In the lung, the mechanisms that functionally link PDGFRĪ± and elastogenic genes had remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several FGF ligands and all four Fgf receptors (Fgfr1ā€“4), alongside splice variants, have been reported in the developing rodent lung . Studies in mice have shown that perturbation of one or more FGF ligands and/or receptors, particularly Fgf9 and Fgf10, can lead to branching defects.…”
Section: Introductionmentioning
confidence: 99%